INTEGRAÇÃO ENTRE GPS E GLONASS - dos Santos, Marcelo Carvalho; Ferreira, Luiz Danilo Damasceno; do Lago, Isabel Franco; Merege Filho, Pedro (Boletim de Ciências Geodésicas, 2004)
O relacionamento entre o GLONASS (Global Navigation Satellite System) e o GPS (Global Positioning System) é explorado neste artigo, que contém uma descrição de suas diferenças e similitudes. Um experimento envolvendo a ocupação, por 14 dias, do marco geodésico RM03, situado na área teste do Laboratório de Geodésia Espacial da UFPR é descrito. Neste experimento, foi empregado um receptor capaz de rastrear dados em ambos os sistemas. Resultados preliminares, envolvendo solução de navegação, calculadas nos dois sistemas, de maneira independente e combinada, são apresentados. Estes resultados indicam uma melhoria na solução quando se integram dados GPS e GLONASS. GPS and Glonass Integration Abstract This paper explores the relationship between GLONASS - Global Navigation Satellite System, and GPS - Global Positioning System. It includes a description of their differences and similarities. A brief description of an experiment which took place in the test area of the Space Geodesy Laboratory of the Federal University of Paraná follows. In this experiment, the geodetic marker RM03 was occupied by a dual frequency GPS/GLONASS receiver for 14 days. Results from a preliminary processing of these data, composed of navigation solution for both systems, combined or not, are shown. These results point out an improvement in the navigation solution when GPS and GLONASS data are integrated.